Rituximab in haematology and oncology in 10 years of experience - Wache, Anna; Gil, Lidia; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2008)
Rituximab, a chimeric anti-CD20 monoclonal antibody, used as a single agent or in combination with chemotherapy, has resulted in significant responses in patients with almost every subtype of B-cell lymphoma. Its modulation effects on the immune system have prompted its use in non-neoplastic diseases. Here, based on 10 years of experience, we summarize label and off-label use of rituximab in oncology and haematology. Rituximab mechanisms of action and resistance are discussed.